Structural Injustices in Swedish Education Academic Selection and Educational Inequalities - Beach, Dennis (Springer International Publishing, 2018)
While Sweden is often viewed as a benchmark for equality within education, this book examines this assumption in greater depth. The author argues that Sweden's education system - even prior to the global spread of neoliberalism in education, meta-policies and privatization - was never particularly equal. Instead, what became apparent was a system that offered advantages to the upper social classes under a sheen of meritocracy and tolerable inequalities. Combining ethnographic and meta-ethnographic methodologies and analyses, the author examines the phenomenon of structural injustice in the Swedish education system both vertically and diachronically across a period of intensive transformation and reform. This revealing volume offers a mode of engagement that will be of value and interest to researchers and students of injustices within education, as well as policy makers and practitioners.